2021
DOI: 10.15201/hungeobull.70.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Directional analysis of drainage network and morphotectonic features in the south-eastern part of Bükk Region

Abstract: The fracture deformations often result in linear morphological elements (lineaments, valleys) on the surface. In many cases, the direction of the lineaments and valleys can be well followed by the strike of the geological structural elements. Therefore, conclusions can be drawn from these directions for regional tectonic processes. Our work aimed to analyse the relationship between the valley and lineament network and the structural elements in the south-eastern part of Bükk Region. We prepared the theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In their recent studies on the directional analysis of drainage networks and morphotectonic features, Pecsmány et al, (2021) found that the results from the assessment of the direction of the valleys, joint set strikes, and lineaments suggest that the formation of the drainage network in the south-eastern part of Bükk Region significantly influences the structural evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In their recent studies on the directional analysis of drainage networks and morphotectonic features, Pecsmány et al, (2021) found that the results from the assessment of the direction of the valleys, joint set strikes, and lineaments suggest that the formation of the drainage network in the south-eastern part of Bükk Region significantly influences the structural evolution.…”
Section: Introductionmentioning
confidence: 99%